Positive Parenting Impact on Parenting Patterns and Attachment Between Parents and Children - Ineu Maryani; Yusi Riksa Yustiana (Balai Diklat Keagamaan Bandung, 2026)
This study aims to analyze the impact of positive parenting on the attachment between parents and children at SMPN 1 Cikalongwetan. A total of 1,021 parents/guardians participated as respondents, with a 68% attendance rate in the parenting program. Data were collected through closed- and open-ended questionnaires and analyzed using descriptive statistics and thematic analysis. The findings show that 78.3% of parents considered the parenting program very important, 19.7% assessed it as fairly important, and only 2% reported “don’t know.” Identified impacts include increased knowledge of adolescent development, adjustments in parenting practices based on children’s needs, strengthened emotional attachment, enhanced supervision of peer interactions, active learning support, reinforcement of moral and religious values, and agreement on gadget use. Moreover, 52% of respondents recommended implementing the program every semester. These findings reinforce the literature on positive parenting as a protective factor against juvenile delinquency and character formation. Parenting programs prove to be relevant as a collaborative strategy between schools and families in fostering a resilient young generation.